2020
DOI: 10.1016/j.ijmedinf.2020.104284
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of CNN to predict the likelihood of COVID-19 using chest X-ray images with preprocessing algorithms

Abstract: Highlights Radiographic chest images can be used to more accurately detect COVID-19 and assess disease severity. Among different imaging modalities, chest X-ray radiography has advantages of low cost, low radiation dose, wide accessibility and easy-to-operate in general or community hospitals. This study aims to develop and test a new deep learning model of chest X-ray images to detect COVID-19 induced pneumonia. For this purpose, we assembled a relatively large chest X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
211
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(256 citation statements)
references
References 28 publications
1
211
0
3
Order By: Relevance
“…Most of these papers used off-the-shelf networks, including ResNet-18 or ResNet-50 16,17,20,26,29,32,37 , DenseNet-121 27,28,31,32,34 , VGG-16 or VGG-19 19,33,35 , Inception 21,38 and EfficientNet 30,39 , with three considering custom architectures 18,25,36 and three using hand-engineered features [22][23][24] . Most papers classified images into the three classes, that is, COVID-19, non-COVID-19 pneumonia and normal 16,19,21,23,25,26,28,30,[32][33][34][35][36][37] , while two considered an extra class by dividing non-COVID-19 pneumonia into viral and bacterial pneumonia 17,29 . ResNet and DenseNet architectures showed better performance than the others, with accuracies ranging from 0.88 to 0.99.…”
Section: Diagnostic Models For Covid-19 Diagnosis Models Using Cxrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these papers used off-the-shelf networks, including ResNet-18 or ResNet-50 16,17,20,26,29,32,37 , DenseNet-121 27,28,31,32,34 , VGG-16 or VGG-19 19,33,35 , Inception 21,38 and EfficientNet 30,39 , with three considering custom architectures 18,25,36 and three using hand-engineered features [22][23][24] . Most papers classified images into the three classes, that is, COVID-19, non-COVID-19 pneumonia and normal 16,19,21,23,25,26,28,30,[32][33][34][35][36][37] , while two considered an extra class by dividing non-COVID-19 pneumonia into viral and bacterial pneumonia 17,29 . ResNet and DenseNet architectures showed better performance than the others, with accuracies ranging from 0.88 to 0.99.…”
Section: Diagnostic Models For Covid-19 Diagnosis Models Using Cxrsmentioning
confidence: 99%
“…We see that 20/32 papers have a reasonable balance between classes (with exceptions being refs. 17,24,26,30,31,33,36,37,40,51,61,62 . However, the majority of datasets were quite small, with 19/32 papers using fewer than 2,000 datapoints for development (with exceptions being refs.…”
Section: Model Evaluation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…As the infection of this virus mainly attacks the patients’ respiratory system [ 19 ], researchers mainly focused on detecting the disease level by finding the infection level using chest X-ray images [ 20 ], chest CT scan images [ 21 ] or cough sound recognition [ 22 ]. Researchers implemented various deep learning and computer vision methods to classify the patients of this infectious disease from healthy patients [ 15 , 23 , 24 ]. Accordingly, numerous deep learning models in the late literature aim to distinguish and order COVID-19 cases.…”
Section: Related Workmentioning
confidence: 99%
“…Abiyev and Ma’aitah [ 35 ] classified the chest X-rays images using CNN for the diagnosis of chest diseases. Heidari et al [ 23 ] demonstrated radio-graphic chest images to detect COVID-19 and assess disease severity. They collected around 8474 chest X-ray dataset images and divided in three groups: non-pneumonia, COVID-19 infected pneumonia and other community-acquired non-COVID-19 infected pneumonia cases.…”
Section: Related Workmentioning
confidence: 99%